KNOWLEDGE AND UTILIZATION OF HEALTH SERVICES OF PEOPLE APPLYING TO A HEALTH CENTER IN UMRANIYE - (:unkn) unknown (NOBEL ILAC, 2009)
Objective: This study was aimed to asses about primary health care (PHC) services and utilization of these services by public in a PHC unit in Umraniye, Istanbul. Material and Method: Descriptive research data collection conducted between May-June 2006, in Dudullu PHC center in Umraniye Participants were 316 people who came to PHC center and accepted to Join the Interview Questionnaire was applied with face to face interview Descriptive statistics, Fisher Exact test and Chi Square test were used in the data analysis. Results: Sixty eight parent of participants were women. Drug prescription was best application reason for PHC unit utilization in last three months, 318% of subjects who need health service utilization were preferred to go to PHC unit while 35.3% preferred state hospitals. Institutional reasons were important factor for application preferences Participants predominantly had the knowledge of outpatient care services (81.3%), immunization services (45.2%), reproductive health and family planning services (23.1%). Outpatient care services (91.4%), immunization (30.6%), find pediatric health services (17.4%) were mostly utilized in PHC unit PHC services utilization significantly differed according to gender, marriage statics, education level, working status and social security status groups (p<0.05). Conclusion: We found that outpatient care, immunization find reproductive health and family planning and child health services were mostly known by our subjects of the study. These services are also the most commonly used services in PHCs.
Keywords: Health center; health services; utilization